1989
DOI: 10.1177/096032718902100102
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent lighting, headaches and eyestrain

Abstract: The weekly incidence of headaches among office workers was compared when the offices were lit by fluorescent lighting where the fluorescent tubes were operated by (a) a conventional switch-start circuit with choke ballast providing illumination that pulsated with a modulation depth of 43-49% and a principal frequency component at 100 Hz; (b) an electronic start circuit with choke ballast giving illumination with similar characteristics; (c) an electronic ballast driving the lamps at about 32 kHz and reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
8

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(149 citation statements)
references
References 12 publications
2
139
0
8
Order By: Relevance
“…107,108 Two studies have found that increasing the operating frequency of the fluorescent lighting system decreases the incidence of eyestrain, headache, and other asthenopic symptoms. 109,110 In particular, Wilkins et al found that the installation of high-frequency ballasts led to a 50% reduction in the reported incidence of eye-strain and headaches in office workers.…”
Section: Arousal and Stressmentioning
confidence: 99%
“…107,108 Two studies have found that increasing the operating frequency of the fluorescent lighting system decreases the incidence of eyestrain, headache, and other asthenopic symptoms. 109,110 In particular, Wilkins et al found that the installation of high-frequency ballasts led to a 50% reduction in the reported incidence of eye-strain and headaches in office workers.…”
Section: Arousal and Stressmentioning
confidence: 99%
“…(2) If so, this would account for the reduced incidence of headache and eye-strain when electronic ballasts were introduced into offices. (17) The absence of effects on visual comfort in this experiment probably reflects the brief exposure time (8 minutes at most before the administration of the visual comfort measure). All the participants reported being relatively comfortable in both flicker conditions.…”
Section: Discussionmentioning
confidence: 78%
“…The evidence does not support changing fluorescent lamp type as a solution to occupants' problems with fluorescent lighting. Field and laboratory studies have more consistently identified other aspects of the lighting system, such as the flicker rate (Veitch & McColl, 1995;Wilkins, Nimmo-Smith, Slater, & Bedocs, 1989) and luminaire design (Hedge, Sims, & Becker, 1995;Katzev, 1992) as levers for solutions to problems with interior lighting. Future research should focus on understanding these effects to characterise high-quality lit environments that meet human needs.…”
Section: Discussionmentioning
confidence: 99%